2010
DOI: 10.1080/00926230903375677
|View full text |Cite
|
Sign up to set email alerts
|

Women's Vibrator Use in Sexual Partnerships: Results From a Nationally Representative Survey in the United States

Abstract: Little is known about women's use of vibrators within sexual partnerships. Data were collected from a population-based, cross-sectional survey of 2056 women aged 18-60 years in the United States. Partnered vibrator use was common among heterosexual-, lesbian-, and bisexual-identified women. Most vibrator users indicated comfort using them with a partner and vibrator use was related to positive sexual function as measured by the Female Sexual Function Index (FSFI). In addition, partner knowledge and perceived l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(67 citation statements)
references
References 22 publications
4
62
1
Order By: Relevance
“…However, this limitation is also a strength in that previous studies have demonstrated online data collection has the potential to limit social desirability bias and result in more accurate and honest responses from study participants 33 34. While challenges exist with establishing truly nationally representative samples of WSW, the similarity of the reported behaviour rates (eg, vibrator/dildo use) to other representative samples suggests that the behaviours of the women in this sample may be similar to those of the women in more representative samples of WSW 17. However, future research should continue to explore the diversity of women's behaviours with other women in assorted samples.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…However, this limitation is also a strength in that previous studies have demonstrated online data collection has the potential to limit social desirability bias and result in more accurate and honest responses from study participants 33 34. While challenges exist with establishing truly nationally representative samples of WSW, the similarity of the reported behaviour rates (eg, vibrator/dildo use) to other representative samples suggests that the behaviours of the women in this sample may be similar to those of the women in more representative samples of WSW 17. However, future research should continue to explore the diversity of women's behaviours with other women in assorted samples.…”
Section: Discussionmentioning
confidence: 94%
“…Response options and language (when appropriate) for the toy use questions were adapted from a US national study on vibrator use17 24–26, and the sexual behaviour questions were adopted from the National Survey of Sexual Health and Behaviour (NSSHB) 1 27. Behaviours that were not assessed in these earlier studies were assessed using the same response options as the other sexual behaviours (‘Past Month’, ‘Past 3 Months’, ‘Past Year’, ‘More than a Year Ago’ and ‘Never Done This’).…”
Section: Main Outcome Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The total score was used as a measure of overall sexual well-being. The scale has been validated for use by women who have sex with women (Herbenick et al, 2010a;Schick, Herbenick, Rosenberger, & Reece, 2011;Tracy & Junginger, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…One potential mode of HPV transmission between women during a sexual encounter is through the sharing of sex toys. Over 50% of women aged 18–60 years report vibrator use, and over 65% of self-identified bisexual women report partnered sex toy use 5. However, the potential for HPV transmission through sex toy use is not well understood, nor are the potential means to prevent transmission through cleaning.…”
Section: Introductionmentioning
confidence: 99%